Evaluation of nurse- and anaesthetist-led sedation for selected transcatheter aortic valve implantation procedures. (2nd November 2022) - Browne, Suzy; Smith, David; Adams, Daniel; Thiruthalil, Sumesh; Pottle, Alison; Bowers, Mark; McGovern, Ian; Mattison, Simon; Smith, Robert; Panoulas, Vasileios; Kabir, Tito; Davies, Simson; et al.
Abstract: Background/Aims: Most transcatheter aortic valve implantation procedures are now performed under conscious sedation, rather than general anaesthetic. This study evaluated nurse-led conscious sedation, compared with anaesthetist-led sedation, to determine the feasibility of the former. Methods: Consecutive patients undergoing transcatheter aortic valve implantation under either nurse-led or anaesthetist-led sedation between July 2018 and September 2021 were reviewed. Assessed outcomes were analysed and compared, including 30-day mortality rate, major vascular access site bleeding, moderate or severe aortic regurgitation, stroke, new pacemaker implantation, duration of procedure and length of stay. Results: A total of 212 patients who underwent nurse-led sedation and 412 who underwent anaesthetist-led sedation were identified. There were no significant differences in risk scores between the two groups. In both groups, incidence of conversion to general anaesthetic was low, with nurse sedatitionists seeking anaesthetist support in 13 (6.2%) cases. Cases with nurse-led sedation had a significantly lower average duration of the procedure (90 minutes vs 111 minutes; P =0.001) and length of stay (2 days vs 3 days, P =0.0002). Conclusions: Nurse-led sedation can be safely incorporated into transcatheter aortic valve implantation practice. Nurse-led sedation delivered similar outcomes to anaesthetist-led sedation, but with shorter procedural times and legnth of stay. This could allow more flexible scheduling, increased capacity and improved access for patients.